1984
DOI: 10.1111/j.1365-2672.1984.tb02351.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of streptococci in a medical laboratory

Abstract: A total of 965 cultures of streptococci received at a reference unit for identification were examined with API-20 Strep kits and also by established methods. The API method, although it needed to be supplemented with additional tests, largely overcame the difficulty that pyogenic streptococci are usually identified by their serological reactions and that biochemical tests are used for the identification of the other streptococci. Representatives of at least 24 established or possible species were identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
41
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(43 citation statements)
references
References 35 publications
2
41
0
Order By: Relevance
“…These isolates have interesting textural technological aptitudes. These results were also described by Colman and Ball (1984) and Idoui and Karam (2008). In a previous study, Bouzar et al (1996) reported that Lb.delbrueckii ssp.bulgaricus CNRZ 1187 and two variants from it produced different yields of neutral heteropolysaccharides when grown in milk.…”
Section: Proteolytic Activitysupporting
confidence: 65%
“…These isolates have interesting textural technological aptitudes. These results were also described by Colman and Ball (1984) and Idoui and Karam (2008). In a previous study, Bouzar et al (1996) reported that Lb.delbrueckii ssp.bulgaricus CNRZ 1187 and two variants from it produced different yields of neutral heteropolysaccharides when grown in milk.…”
Section: Proteolytic Activitysupporting
confidence: 65%
“…These species have interesting textural technological aptitudes; this type of result was also described by (Colman and Ball 1984). In a previous study, (Bouzar et al, 1996) reported that L. delbrueckii ssp.…”
Section: Discussionmentioning
confidence: 64%
“…Additional tests were performed to confirm the identification. These included the catalase reaction, which was performed on an 18-h culture grown on serum glucose agar in 5% CO 2 , and the test for dextran-levan production (12).…”
Section: Strainsmentioning
confidence: 99%